Acute Pancreatitis in Japan: Comparison of Before and After Revision of the Clinical Guidelines. Issue 3 (March 2022) - Ikeda, Mio; Hamada, Shin; Kikuta, Kazuhiro; Takikawa, Tetsuya; Yoshida, Naoki; Matsumoto, Ryotaro; Tanaka, Yu; Kataoka, Fumiya; Sasaki, Akira; Tarasawa, Kunio; Fujimori, Kenji; Fushimi, Kiyohide; et al.
Abstract : Objectives: Cases of acute pancreatitis (AP) are increasing worldwide, and mortality remains high in severe cases. In 2015, the Japanese guidelines for the management of AP were revised. We aimed to clarify the clinical practice of AP in Japan and its trend during the revision of the guidelines using a Japanese nationwide administrative database. Methods: We retrospectively analyzed 102, 119 patients with AP who were hospitalized between April 2014 and March 2018. The study period was divided into the first period (the time before the revision: fiscal years 2014 and 2015) and second period (after the revision: 2016 and 2017). Results: Severe cases of AP accounted for 27.7% of total cases. The in-hospital mortality in severe cases was 5.7%. The mortality within 14 days of admission improved from 3.2% in the first period to 2.6% in the second period ( P = 0.022). Referred patients had more severe diseases and a higher mortality. The mortality in patients who underwent endoscopic ultrasound-guided fistuloplasty for local complications (11.6%) was lower than that in patients who underwent percutaneous drainage (23.4%) or AP surgery (22.6%) ( P < 0.001). Conclusions: We clarified the clinical practice of AP including the improved mortality after the revision of the guidelines.